The risk of adverse impact in selections based on a test with known effect size - DE CORTE, Wilfried (Institutional Knowledge at Singapore Management University, 2005)
The authors derive the exact sampling distribution function of the adverse impact (AI) ratio for single-stage, top-down selections using tests with known effect sizes. Subsequently, it is shown how this distribution function can be used to determine the risk that a future selection decision on the basis of such tests will result in an outcome that reflects the presence of AI. The article therefore provides test and selection practitioners with a valuable tool to decide between alternative selection predictors.